2013
DOI: 10.1096/fj.13-231274
|View full text |Cite
|
Sign up to set email alerts
|

Greatly improved survival and neuroprotection in aquaporin‐4‐knockout mice following global cerebral ischemia

Abstract: Aquaporin-4 (AQP4), the principal water channel in astrocytes, is involved in brain water movement, inflammation, and neuroexcitation. In this study, there was strong neuroprotection in mice lacking AQP4 in a model of global cerebral ischemia produced by transient, bilateral carotid artery occlusion (BCAO). Survival and neurological outcome were greatly improved in the AQP4(-/-) vs. AQP4(+/+) mice after occlusion, with large and robust differences in both outbred (CD1) and inbred (C57bl/6) mouse strains withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…We previously reported greatly improved outcome in AQP4 knockout mice following focal ischemia produced by permanent MCAO [16], and more recently, improved outcome in AQP4 knockout mice following global ischemia produced by transient carotid artery occlusion [1, 10]. Also, several correlative studies reported reduced cerebral edema following ischemia with reduced AQP4 expression, including propofol and edaravone administration, protein kinase C activation [4], hypertonic saline administration [30], and endothelin-1 overexpression [13].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported greatly improved outcome in AQP4 knockout mice following focal ischemia produced by permanent MCAO [16], and more recently, improved outcome in AQP4 knockout mice following global ischemia produced by transient carotid artery occlusion [1, 10]. Also, several correlative studies reported reduced cerebral edema following ischemia with reduced AQP4 expression, including propofol and edaravone administration, protein kinase C activation [4], hypertonic saline administration [30], and endothelin-1 overexpression [13].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that AQP4 may be important in the chronic phase of the post-ischemic recovery process. Research conducted by Katada et al [37] and Shi et al [40] may yield different conclusions, and several factors may explain this discrepancy. First and foremost, different models used may have caused these inconsistencies.…”
Section: Current Research Investigating the Effects Of Aqp4 On Neuroimentioning
confidence: 95%
“…The BCAO model has been widely used to study the mechanisms of neuronal death and cognitive impairments after ischemia. Katada et al [37] suggested that there was strong neuroprotection in mice lacking AQP4 in a model of global cerebral ischemia produced by transient BCAO, and the neuroprotective effects of AQP4 deletion in global cerebral ischemia involved reduced astrocyte swelling and brain water accumulation, resulting in reduced blood-brain barrier (BBB) disruption, inflammation, and neuron death. Similarly, Fukuda et al [38] observed that siAQP4 treatment after TBI resulted in a decrease in AQP4 associated with less BBB disruption, less edema, and better behavioral outcomes compared to the control group at up to 2 months post-injury.…”
Section: Current Research Investigating the Effects Of Aqp4 On Neuroimentioning
confidence: 99%
“…Notwithstanding the complexities of cytotoxic and vasogenic mechanisms, the main finding of this study was a small beneficial effect of AQP4 deletion in TBI. The beneficial effect was very small compared with the robust beneficial effects of AQP4 deletion in water intoxication, a model of pure cytotoxic edema 4 , or in focal 32 or global33,34 cerebral ischemia, where cytotoxic edema predominates. The small beneficial effect of AQP4 deletion in the CCI model here may be the consequence of mixed cytotoxic/vasogenic edema mechanisms in which AQP4 has opposing actions.…”
mentioning
confidence: 90%